The EU’s Arctic Strategy: Interests and Priorities - O. V. Aleksandrov (Vestnik MGIMO-Universiteta, 2013)
This article deals with the Arctic strategy of the European Union. The main task of the author is to show the development of the EU’s Arctic policy during the previous 5 years, to analyze motivations of the EU’s actions in the Arctic, to assess the foreign policy resources which are at the disposal of Brussels to carry out the EU’s Arctic policy, and therefore to demonstrate the growing role of the EU in the Arctic. Apart from that, the author attempts to answer a question to what extent the EU’s interests in the Arctic coincide with or contradict interests of Russia and other Arctic states.